Cobalt release from earrings and piercing jewellery - analytical results of a German survey - Uter, Wolfgang; Schmid, Matthias; Schmidt, Oliver; Bock, Constance; Wolter, Jörg (Contact Dermatitis, 2014)
Contact sensitization to cobalt is common. Some industrial exposures have been identified, but cobalt allergy is also often diagnosed in 'non-occupational' patients. Exposure of consumers is largely unexplained.To present the analytical results on cobalt release from earrings and piercing jewellery sampled in a German Federal surveillance scheme.Two German state laboratories analysed cobalt release, after immersion in artificial sweat according to EN 1811, along with nickel release in 87 pieces of jewellery, which were mostly taken apart for separate examination of piercing posts (n = 139), clasps (n = 51), and/or decorative items (n = 52). The distribution of cobalt release was described by the use of Kaplan-Meier analysis, taking into account that the majority of measurements were left-censored, that is, below the limit of quantification.Thirty-eight of 87 earrings and piercing jewellery items had at least one part releasing cobalt. The median cobalt release was estimated as 0.013 µg/cm(2) /week, and 75% of parts released up to 0.085 µg/cm(2) /week. Release varied somewhat between the three parts, with, for example, 22.1% of posts releasing >= 0.2 µg/cm(2) /week.Cobalt release from earrings and piercing jewellery, in particular from piercing posts, is considerable. Scientifically based exposure limits should be set, as in the case of nickel.
EVALuna2:5459